A qualitative study of stakeholder views regarding participation in locally commissioned enhanced optometric services. Issue 5 (29th May 2014) - Konstantakopoulou, E; Harper, R A; Edgar, D F; Lawrenson, J G
Abstract : Objectives: To explore the views of optometrists, general practitioners (GPs) and ophthalmologists regarding the development and organisation of community-based enhanced optometric services. Design: Qualitative study using free-text questionnaires and telephone interviews. Setting: A minor eye conditions scheme (MECS) and a glaucoma referral refinement scheme (GRRS) are based on accredited community optometry practices. Participants: 41 optometrists, 6 ophthalmologists and 25 GPs. Results: The most common reason given by optometrists for participation in enhanced schemes was to further their professional development; however, as providers of 'for-profit' healthcare, it was clear that participants had also considered the impact of the schemes on their business. Lack of fit with the 'retail' business model of optometry was a frequently given reason for non-participation. The methods used for training and accreditation were generally thought to be appropriate, and participating optometrists welcomed the opportunities for ongoing training. The ophthalmologists involved in the MECS and GRRS expressed very positive views regarding the schemes and widely acknowledged that the new care pathways would reduce unnecessary referrals and shorten patient waiting times. GPs involved in the MECS were also very supportive. They felt that the scheme provided an 'expert' local opinion that could potentially reduce the number of secondary care referrals. Conclusions: The results of this study demonstrated strong stakeholder support for the development of community-based enhanced optometric services. Although optometrists welcomed the opportunity to develop their professional skills and knowledge, enhanced schemes must also provide a sufficient financial incentive so as not to compromise the profitability of their business.